What do patients say about their physicians? an analysis of 3000 narrative comments posted on a German physician rating website. - Emmert, Martin; Meier, Florian; Heider, Ann-Kathrin; Dürr, Christoph; Sander, Uwe (Health policy (Amsterdam, Netherlands), 2014)
BACKGROUND Physician rating websites (PRWs) could be shown to have an impact on physician choice making. However, little research has been carried out to assess the content and nature of narrative comments. OBJECTIVE The aim of this study was to explore the concerns of patients who commented on physician care and to address and enhance patient satisfaction. METHODS Content analysis of 3000 randomly selected narrative comments from the German PRW, jameda, from 2012. We therefore developed a theoretical categorization framework addressing physician, staff, and practice related patient concerns. FINDINGS In total, 50 sub-categories addressing the physician (N=20), the office staff (N=13), and the practice (N=17) were derived from the content of all comments. The most frequently mentioned concerns were assessing the professional competence of the physician (63%, N=1874) and friendliness of the physician (38%, N=1148). Thereby, 80% of all comments (mean length 45.3 words ± 42.8) were classified as positive, 4% as neutral and 16% as negative. CONCLUSION Users of the German PRW, jameda, are mostly satisfied with their physicians. However, physicians should focus on the time spent with the patients, waiting time, as well as on taking the patients more seriously.